2012
DOI: 10.1160/th11-09-0624
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine induces endothelial tissue factor expression via phosphatidylinositol 3-kinase inhibition

Abstract: SummaryTissue factor (TF) is the key activator of coagulation and is involved in acute coronary syndromes. Caffeine is often reported to increase cardiovascular risk; however, its effect on cardiovascular morbidity and mortality is controversial. Hence, this study was designed to investigate the impact of caffeine on endothelial TF expression in vitro. Caffeine concentration-dependently enhanced TF protein expression and surface activity in human endothelial cells stimulated by tumour necrosis factor (TNF)-α o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Therefore, we tested whether dendrimers could inhibit PI3K, such that in the absence of negative regulation, LPS-induced inflammatory reactions including PCA expression could continue to propagate. A recent study by Gebhard et al , describing enhancement of TNF-mediated TF expression by the cationic small molecule caffeine, further fueled this hypothesis and led us to study dendrimer effects on PI3K [38]. We found that cationic PAMAM dendrimers completely abrogated kinase activity of rPI3K (Figure 7).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Therefore, we tested whether dendrimers could inhibit PI3K, such that in the absence of negative regulation, LPS-induced inflammatory reactions including PCA expression could continue to propagate. A recent study by Gebhard et al , describing enhancement of TNF-mediated TF expression by the cationic small molecule caffeine, further fueled this hypothesis and led us to study dendrimer effects on PI3K [38]. We found that cationic PAMAM dendrimers completely abrogated kinase activity of rPI3K (Figure 7).…”
Section: Discussionsupporting
confidence: 53%
“…Some cytokines, specifically TNF and IL-1, are known to induce TF expression [38,50]. In our earlier studies, we observed an enhancement of both TNF and IL-1 by amine-terminated PAMAM dendrimers [Dobrovolskaia MA, Potter T, McNeil SE, Unpublished Data].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…PI3Ks have been linked to an extraordinarily diverse group of cellular functions, including inflammation and coagulation ( 95 , 96 , 97 ). An earlier study has shown that PI3K is crucial in mediating the prothrombotic potential of ECs ( 98 ). In vivo studies have shown that inhibition of PI3K strongly enhances activation of ECs, upregulates LPS-induced coagulation and inflammation, and reduces the survival time of mice ( 97 ).…”
Section: Discussionmentioning
confidence: 99%